A brief review on different plant parts used as immunity boosting agent - Debgopal Ganguly; Soumyadip Ghosh; Madhumita Banerjee; Anasuya Mandal; Sarmistha Panja; Ananta Choudhury (Journal of Applied Pharmaceutical Research, 2022)
A strong immune system is essential to keep a person healthy. Every person should incorporate specific food items into their diet that can strengthen their immune system. Mother Nature has a bag full of plants and trees whose different parts contain different ingredients that can act as immune boosters. Tulsi is a small herb, found in many parts of India and can be grown in our homes too. The leaves of Tulsi have different properties like antimicrobial, antipyretic, anti-inflammatory, and many more. 5-6 leaves of Tulsi daily help to build our immune system. Giloy is an herbaceous vine found in the tropical regions of different Indian subcontinents. The heart-shaped leaves and reddish fruit of Giloy have many active ingredients like alkaloids, glycosides, phytosterols, etc. which help to attain anti-inflammatory, antipyretic, antioxidant properties. 2-3 tablespoons of Giloy juice daily helps to boost our immune system and increase the ability of our body to fight various infectious diseases. Garlic is used in a variety of dishes we cook garlic bulb is a great supplement known to boost the immune system functioning. Active compound present in garlic helps to reduce blood pressure improve cholesterol levels and can also lower the risk of heart diseases. Garlic bulbs can also reduce cold and flu symptoms. The various vitamins present in garlic also add more effect to its immunity-boosting property. Citrus lemon is found primarily in the north-eastern part of India, China or Myanmar, Italy, Spain. It has various phytochemicals such as terpenes, tannins, polyphenols, etc. is considered a rich of all essential vitamins to enrich our immune system and also provide therapeutic benefits